PENGELOLAAN SISTEM PERIZINAN DALAM RANGKA MEWUJUDKAN IKLIM USAHA BAGI USAHA MIKRO, KECIL DAN MENENGAH DI DAERAH - Teuku Ahmad Yani (Universitas Teuku Umar, 2015)
The licensee is interesting point for business entity and goverment. The system of district licensee should make good condition for every side. Therefore, the local goverment should do reformation and deregulation about the local of licensee. The license is related with retribution that must be paid by business when need licensee from local goverment. For making the positive thinking the system regarding license, the local goverment should do not always related with retibution. Key Word: Licensee, retribution, local goverment